Social Health Insurance and the Use of Formal and Informal Care in Developing Countries: Evidence from Ghana's National Health Insurance Scheme. Issue 7 (3rd July 2019) - Abrokwah, Stephen O.; Callison, Kevin; Meyer, Donald J.
Abstract: This paper studies the relationship between the use of formal and informal health care in a developing country setting by examining the introduction of a social health insurance scheme in Ghana. We estimate the effects of gaining coverage on changes in care seeking behaviour and show how these effects differ by age and wealth status. District-level differences in the implementation of the insurance scheme provide exogenous variation in access to insurance and allow us to address issues with selection into coverage. Results indicate that insurance access strongly increased use of formal care and reduced out-of-pocket expenditures on health services.